2013
DOI: 10.1007/s12020-013-9993-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of high-sensitivity C-reactive protein and fetuin-A levels before and after treatment for subjects with subclinical hyperthyroidism

Abstract: This study was designed to show the effect of propylthiouracil treatment on sCD40L, high-sensitivity C-reactive protein, and fetuin-A levels on subjects with subclinical hyperthyroidism. After checking sCD40L, high-sensitivity C-reactive protein, and fetuin-A levels of 35 patients with subclinical hyperthyroidism, each was given 50 mg tablets of propylthiouracil three times daily. After 3 months, sCD40L, high-sensitivity C-reactive protein, and fetuin-A levels were then compared to the levels before treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Two studies evaluated CRP levels in SH subjects and both reported no change in CRP levels compared to euthyroid group [11,12]. Bilgir et al also evaluated CRP levels 3 months after treatment with propyl thiouracil and reported no significant change in CRP levels after using anti-thyroid drug [11]. In our study, we also found no significant change in CRP levels after carbimazole suggesting absence of inflammatory state in SH.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Two studies evaluated CRP levels in SH subjects and both reported no change in CRP levels compared to euthyroid group [11,12]. Bilgir et al also evaluated CRP levels 3 months after treatment with propyl thiouracil and reported no significant change in CRP levels after using anti-thyroid drug [11]. In our study, we also found no significant change in CRP levels after carbimazole suggesting absence of inflammatory state in SH.…”
Section: Discussionsupporting
confidence: 49%
“…Only one study reported higher CRP in 250 hyperthyroid subjects compared to controls but the same study reported much higher CRP levels in hypothyroid subjects [10]. Two studies evaluated CRP levels in SH subjects and both reported no change in CRP levels compared to euthyroid group [11,12]. Bilgir et al also evaluated CRP levels 3 months after treatment with propyl thiouracil and reported no significant change in CRP levels after using anti-thyroid drug [11].…”
Section: Discussionmentioning
confidence: 99%
“…Fetuin-A (α-Heremans-Schmid glycoprotein) is a circulating glycoprotein secreted by the liver into the circulation. Links between fetuin-A and cardiovascular disease, insulin resistance, diabetes mellitus, metabolic syndrome and non-alcoholic fatty liver have been reported ( 15 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…While an increase in fibrinogen concentration was reported in several studies, Hp concentration, the ESR and CRP (a major acute phase reactant in humans) were not significantly different between hyperthyroid and euthyroid patients. [24][25][26][27][28] The same appears to be true for cats. As demonstrated here, hyperthyroidism induced an increase in AGP concentration and, to a lesser extent, in SAA and Hp concentrations.…”
Section: Discussionmentioning
confidence: 80%